Pembebasan dalam Teologi Feminis:: Sebuah Analisis terhadap Catcalling dalam Rangka Pencapaian Keadilan Gender - Mettang, Marta; Naomi Sampe (Jurnal Salvation, 2024)
Abstract: Catcalling has become a phenomenon that threatens, disturbs and challenges women's dignity, leading to gender inequality. This research offers the intrinsic values found in women based on a feminist theological perspective as an integration of men's understanding that women have the same values as men in general in order to achieve gender equity and justice. This research aims to analyze catcalling in the context of achieving gender justice through the lens of feminist theology. The research method used is a qualitative method by collecting and analyzing data through literature study. This research covers women's intrinsic values based on a feminist theological perspective, the negative impact of catcalling, and the concept of liberation in feminist theology. The results of the discussion show that catcalling, as a form of gender inequality, creates an unsafe environment for women in public spaces. Feminist theology emphasizes the importance of women's intrinsic values, such as dignity, justice, and diversity, in achieving gender justice. Women's liberation in feminist theology also includes the struggle against gender inequality and social violence, including catcalling. Thus, this research contributes to the understanding and efforts to overcome catcalling as a form of verbal sexual harassment that harms women. By understanding the intrinsic values of women in feminist theology, it is hoped that a society that is more just, inclusive and respects the dignity of every individual regardless of gender can be realized. This research can be the basis for concrete steps in building gender justice and responding to challenges of inequality in everyday life such as catcalling. Abstrak: Catcalling telah menjadi fenomena yang mengancam, resahkan dan menantang martabat perempuan yang mengarah pada kesenjangan gender. Penelitian ini menawarkan nilai-nilai intriksik yang terdapat pada perempuan berdasarkan perspektif teologi feminis sebagai integrasi pemahaman laki-laki bahwa perempuan itu memiliki nilai yang sama dengan laki-laki secara umum demi tercapainya keadilan dan keadilan gender. Penelitian ini bertujuan untuk menganalisis catcalling dalam rangka pencapaian keadilan gender melalui lensa teologi feminis. Metode penelitian yang digunakan adalah metode kualitatif dengan mengumpulkan dan menganalisis data melalui studi kepustakaan. Penelitian ini mencakup nilai-nilai intrinsik perempuan berdasarkan perspektif teologi feminis, dampak negatif catcalling, dan konsep pembebasan dalam teologi feminis. Hasil pembahasan menunjukkan bahwa catcalling, sebagai bentuk ketidaksetaraan gender, menciptakan lingkungan yang tidak aman bagi perempuan di ruang publik. Teologi feminis menegaskan pentingnya nilai-nilai intrinsik perempuan, seperti martabat, keadilan, dan keberagaman, dalam mencapai keadilan gender. Pembebasan perempuan dalam teologi feminis juga mencakup perjuangan melawan ketidaksetaraan gender dan kekerasan sosial, termasuk catcalling. Dengan demikian, penelitian ini adalah memberikan kontribusi pada pemahaman dan upaya mengatasi catcalling sebagai bentuk pelecehan seksual verbal yang merugikan perempuan. Dengan memahami nilai-nilai intrinsik perempuan dalam teologi feminis, diharapkan dapat terwujud masyarakat yang lebih adil, inklusif, dan menghormati martabat setiap individu tanpa memandang jenis kelamin. Penelitian ini dapat menjadi landasan bagi langkah-langkah konkret dalam membangun keadilan gender dan merespons tantangan ketidaksetaraan dalam kehidupan sehari-hari seperti catcalling.